La direction des sociétés anonymes en droit sénégalais comparée aux droits français anglais et américain - Dieng, Françoise (Université Paris 1, 1995)
Le Sénégal, par la loi n°85-40 du 29 juillet 1985, s'est doté de son premier code des sociétés commerciales depuis son accession à l'indépendance. Cette loi s'inspire des droits français, anglais et américain quant à la direction des sociétés anonymes. C'est à ces droits que sera comparée la direction des sociétés anonymes en droit sénégalais en ses divers aspects que sont les pouvoirs des dirigeants sociaux, leur statut juridique leurs devoirs et leur responsabilité.
Keywords: Approche comparée; Droit commercial; Droit comparé; Droit des sociétés commerciales; Sociétés anonymes; Sénégal

Fiduciary duties of company directors with specific regard to corporate opportunities - Havenga, Michele Kyra (University of South Africa, 1995)
South African company law is currently the object of comprehensive review. One o f the areas under scrutiny is that of corporate governance. Control over management is vital in the interests of the company itself, its shareholders and its creditors. Effective accountability should be balanced against the need to allow those who manage a certain measure of freedom and discretion in the exercise of their function. Company directors are subject to various duties. This thesis concentrates on their fiduciary obligation. It is suggested that this sui generis obligation is owed to the company as a separate entity. Interests of other groups may sometimes merit con sideration. Against the background of a comparative investigation, a "corporate opportunity" is defined as any property or economic opportunity to which the com pany has a claim. South African law protects a company’s claim to an opportunity if it is in the company’s line of business and if the company has justifiably been relying upon the director(s) to acquire it or to assist in its acquisition for the company. The application of established fiduciary principles suffice to resolve corporate opportunity matters. Essentially the application of these rules amount to a determination whether the director has complied with his fundamental duty to act in the company’s best interests. There seems to be no need for a separate doctrine of corporate opportunities.' A director should only be absolved from liability on account of the company’s inability to pursue an opportunity or its rejection by the company if there was no real conflict of interest. The appropriation of corporate opportunities should not be ratifiable, both because the ratification constitutes a fraud on the minority, and because the decision to ratify cannot be regarded as being in the interests of the company. The relationship between the appropriation of corporate opportunities, misuse of confidential information and competition is investigated. These aspects fre quently overlap, but should be distinguished because their bases, and accordingly their appropriate remedies, may differ. Effective control may benefit by a restatement of directors’ fiduciary duties in the Companies Act. To this end certain amendments to the Act are recommended.
Keywords: Codes of conduct; Competition; Confidential information; Conflicts of interest; Corporate opportunities; Corporate opportunity doctrine; Corporation law; Directors of corporations; Fiduciary duties; Multiple directorships; Secret profits

Les Groupes de sociétés et le droit : contribution à la recherche sur la notion de pouvoir en droit privé - Sakho, Abdoulaye (Université Cheikh Anta Diop, 1993)
Keywords: Droit privé; Groupe de sociétés; Pouvoir